DESIGN BUILD LIBRARY INFORMATION SYSTEM BASED FOR SANTA MARIA 2 HIGH SCHOOL BANDUNG - Candra Perdana; Ari Purno Wahyu Wibowo (Jurnal Darma Agung, 2022)
Data collection is generally done manually, but this manual method has drawbacks, namely data collection becomes ineffective, not neatly arranged, and searching for data takes a lot of time. Likewise with library management at Santa Maria 2 High School Bandung, data collection is still manual so there are often many errors , therefore an information system is needed that can manage book collection data, library member data, book borrowing data, book return data and fines data for members who are late in returning books, which aims to improve the performance of library managers to be more effective in managing library data, and also to increase the reading interest of library members, namely Santa Maria 2 Bandung High School students themselves. The research method used is research and development with the sql website development method. The data collection methods used were interviews and observations. The interview method is to determine user needs, while the observation is for testing aspects of performance efficiency. The results of this study are (1) the system is proven that the level of feasibility of a web-based library information system using PHP and a MYSQL database server. (2) The test results prove that the level of feasibility of a web-based library information system in the aspect of usability for small groups is 8 1.22 % with very feasible criteria and large groups 9 0.2 % with very feasible criteria , and aspects of performance efficiency 9 6.64 with grade A.